Dat : tackling life and the NFL - Nguyen, Dat, 1975- (Texas A & M University Press, 2005)
Presents the author's first-hand account of his experiences playing football in the NFL, the first player of Vietnamese descent to achieve that goal, and includes information on his faith, his family, and his career.